2015
DOI: 10.1107/s1399004715018635
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and kinetic studies of a tetrameric type II β-carbonic anhydrase from the pathogenic bacteriumVibrio cholerae

Abstract: Carbonic anhydrase (CA) is a zinc enzyme that catalyzes the reversible conversion of carbon dioxide to bicarbonate (hydrogen carbonate) and a proton. CAs have been extensively investigated owing to their involvement in numerous physiological and pathological processes. Currently, CA inhibitors are widely used as antiglaucoma, anticancer and anti-obesity drugs and for the treatment of neurological disorders. Recently, the potential use of CA inhibitors to fight infections caused by protozoa, fungi and bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 39 publications
2
71
0
Order By: Relevance
“…However, no esterase activity was detected so far for enzymes belonging to the other five CA genetic families. The 3D fold of the five CA classes is very different: a-CAs are normally monomers and rarely dimers [21][22][23] ; b-CAs are dimers 24 , tetramers or octamers; g-CAs are trimers. The only z-CA crystallized so far has three slightly different active sites on the same polypeptide chain, whereas no X-ray crystal structures of d-and Z-and CAs are available so far.…”
Section: Carbonic Anhydrase Familymentioning
confidence: 99%
“…However, no esterase activity was detected so far for enzymes belonging to the other five CA genetic families. The 3D fold of the five CA classes is very different: a-CAs are normally monomers and rarely dimers [21][22][23] ; b-CAs are dimers 24 , tetramers or octamers; g-CAs are trimers. The only z-CA crystallized so far has three slightly different active sites on the same polypeptide chain, whereas no X-ray crystal structures of d-and Z-and CAs are available so far.…”
Section: Carbonic Anhydrase Familymentioning
confidence: 99%
“…[60][61][62][63]VchCA was shown to possess a significant catalytic activity for the reaction that converts the CO 2 [63]Moreover, our subsequent work allowed the crystallization of VchCAβ, showing that the zinc ion is coordinated by four amino acid residues, Cys42, Asp44, His98, Cys101, in an approximately tetrahedral geometry. VchCAβ belongs to the type II subclass β-CAs, characterized by four protein-derived ligands that coordinate the catalytic zinc ion, contrary to the type I β-CAs that have only two cysteines and one histidine residues in the zinc coordination sphere with a fourth coordination site occupied by a water molecule/hydroxide ion acting as nucleophile in the catalytic cycle [63]. The crystal structure was determined at pH 8.0, when a bicarbonate ion bound in a non-catalytic binding pocket close to the zinc ion was also observed [48].…”
Section: Vibrio Choleraementioning
confidence: 99%
“…The crystal structure was determined at pH 8.0, when a bicarbonate ion bound in a non-catalytic binding pocket close to the zinc ion was also observed [48]. At pH 8.3, the enzyme showed a significant catalytic activity for the physiological reaction of CO 2 [63].This is in fact the situation for all type II β-CAs, which at pH values > 8 become of type I, with the asp residue being involved in a salt bridge with a neighboring conserved Arg, and an incoming water molecule/hydroxide ion replacing the Asp residue [49][50][51][52][53][54]. Recently it was reported that sodium bicarbonate induces cholera toxin (CT) expression [64,65].…”
Section: Vibrio Choleraementioning
confidence: 99%
“…[57][58][59][60] (iii) The inhibitory action against BpsCAc was very low for the following compounds: 8, 11-13, 16 and 24, which had K I s in the range of 10,800-24,500 nM. Again, they belong to heterogeneous classes of sulfonamides, with aromatic monosulfonamides (8,16,24), disulfonamides (11,12), and a heterocylic sulfonamide derivative, deacetylated acetazolamide 13 (Table 1). (iv) A number of the investigated sulfonamides did not inhibit BpsCAc up to 50 lM, which is the maximum concentration of inhibitor in the assay system.…”
Section: 53mentioning
confidence: 99%
“…[5][6][7][8][9] This superfamily includes seven distinct classes known as the a-, b-, c-, d-, f-, g-and ɵ-CAs. [10][11][12][13][14][15][16][17][18] These enzymes are involved in many physiologic processes, such as photosynthesis, respiration, CO 2 transport, as well as metabolism of xenobiotics (e.g., cyanate in Escherichia coli). Some of the catalytically active a-and ɵ-CAs can also catalyze the hydrolysis of esters, such as 4-nitrophenyl acetate (4-NpA).…”
Section: àmentioning
confidence: 99%